Visualization of user's attention on objects in 3D environment using only eye tracking glasses. Issue 2 (30th March 2020) - Li, Ting-Hao; Suzuki, Hiromasa; Ohtake, Yutaka
Abstract: Eye tracking technology is widely applied to detect user's attention in a 2D field, such as web page design, package design, and shooting games. However, because our surroundings primarily consist of 3D objects, applications will be expanded if there is an effective method to obtain and display user's 3D gaze fixation. In this research, a methodology is proposed to demonstrate the user's 3D gaze fixation on a digital model of a scene using only a pair of eye tracking glasses. The eye tracking glasses record user's gaze data and scene video. Thus, using image-based 3D reconstruction, a 3D model of the scene can be reconstructed from the frame images; simultaneously, the transformation matrix of each frame image can be evaluated to find 3D gaze fixation on the 3D model. In addition, a method that demonstrates multiple users' 3D gaze fixation on the same digital model is presented to analyze gaze distinction between different subjects. With this preliminary development, this approach shows potential to be applied to a larger environment and conduct a more reliable investigation. Graphical Abstract: